Current Fish Feed Status and Development of New Feeding Technologies for Aquaculture Growth and Development in Kenya: Rapid Review - Mungai, Daniel; Omondi, Argwings; Omweno, Jacob; Outa, Nicholas; Munguti, Jonathan (My University, 2023)
Aquaculture has emerged as a promising sector for addressing the ever-increasing demand for fish protein in Kenya, where over 50% of fish consumption is reliant on imports. However, the sustainable growth and development of aquaculture in Kenya are significantly influenced by the availability and quality of fish feed, which constitutes over 50% of the total production costs. The current fish feed status in Kenya is characterized by several challenges, including limited avail-ability of high-quality feed ingredients, high feed costs, and inconsistent feed quality and nutrient composition. These challenges pose significant constraints to the efficient production of healthy and marketable fish, limiting the full potential of aquaculture growth in Kenya. To address these challenges, efforts are being made towards the development of new feed formulations and feeding technologies that can improve the efficiency and sustainability of fish feed production in Kenya. This includes the utilization of locally available feed ingredients, such as agricultural by-products and aquatic macrophytes, to develop cost-effective and nutritionally balanced feed formulations. Moreover, research is underway to optimize feed processing techniques, such as extrusion, pelleting, and encapsulation, to improve feed quality, stability, and digestibility. Additionally, innovative feeding methods, such as automated feeding systems and precision feeding, are being explored to minimize feed wastage and maximize feed utilization, thereby enhancing fish growth and reducing production costs. The development of new feeding technologies for aquaculture growth and development in Kenya holds great potential to address the challenges associated with fish feed availability, quality, and cost. By optimizing feed formulations, processing techniques, and feeding methods, the aquaculture sector in Kenya can improve its productivity, profitability, and sustainability. However, further research, investment, and collaboration among stakeholders, including government, research institutions, feed manufacturers, and farmers, are essential for the successful implementation and adoption of these new feeding technologies to drive the growth and development of aquaculture in Kenya.
Keywords: Aquaculture growth; Fish feed status; New feeding tech-nologies